Analysis of the Legality of the Kris (Standard Inpatient Class) System from the Perspective of Health Administration Law - Yudhi Hertanto; Anna Veronica Pont; Johannes Triestanto; Habibi; Mohamad Fadli Dg Patompo (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
The Standard Inpatient Class (KRIS) policy represents a significant reform in Indonesia’s national health service system, as stipulated in Presidential Regulation Number 59 of 2024, which replaces the former inpatient class system (Classes 1, 2, and 3) under the National Health Insurance (JKN) program administered by BPJS Kesehatan. The introduction of KRIS is intended to promote principles of equity, equal access, and non-discrimination in health services, while also streamlining the administrative structure of inpatient care in hospitals. This article aims to examine the legal validity of the KRIS system from the perspective of health administrative law, focusing on its legal foundation, governmental administrative authority, implementation mechanisms within healthcare facilities, and legal protection for both patients and hospitals. This study employs a normative juridical approach using library-based research on relevant legislation and national academic journals. The analysis is conducted by examining legal norms governing KRIS and their implications for health administration governance. The findings indicate that, from a normative standpoint, the KRIS system possesses a strong and legitimate legal basis as a state administrative policy in the health sector. Nevertheless, its practical implementation faces several challenges, including hospital infrastructure readiness, funding limitations, disparities in the capacity of healthcare facilities across regions, and potential administrative issues related to supervision and compliance enforcement. Furthermore, stronger technical regulations and more effective oversight mechanisms are required to ensure that the objectives of KRIS particularly legal protection and equal service provision for JKN participants are fully realized. Therefore, policy synchronization, reinforcement of governmental roles, and enhancement of healthcare facility capacity are essential factors for the successful implementation of the KRIS system in Indonesia.